Feasibility study of stacking operations on microbial fuel cell - Chan, Wei Ping. (2011)
Bioelectricity generation from biomass by using bacteria in a fuel cell reactor is becoming popular since the increasing demand and price of fossil fuels. Microbial fuel cells (MFCs) can be used to generate electricity from various forms of biodegradable organic matter but with limited voltage production for a single MFC. This study focused on the feasibility of stacking operations for MFCs to achieve desired power output for practical applications. Single chamber Microbial Fuel Cell (MFC) with an air cathode was used in this study. Power density produced from various stack configurations (series, parallel, and series & parallel) met the expectation for fuel cells as power source. Nevertheless, fuel starvation, high current density requirement and any other factors that could result in incompatible power output when stacking that included a series connection should be avoided. Turning MFCs into a load instead of part of the power source of a system as electrolysis cell resulting in the diminished overall power output due to voltage reversal and oxygen production from partial electrolysis at anode greatly reduced the ability of anaerobic microorganism to carry out biochemical reaction to generate electrons.